2014
DOI: 10.1073/pnas.1324128111
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing identifies rare variants associated with Noonan syndrome

Abstract: Noonan syndrome (NS) is a relatively common genetic disorder, characterized by typical facies, short stature, developmental delay, and cardiac abnormalities. Known causative genes account for 70-80% of clinically diagnosed NS patients, but the genetic basis for the remaining 20-30% of cases is unknown. We performed nextgeneration sequencing on germ-line DNA from 27 NS patients lacking a mutation in the known NS genes. We identified gainof-function alleles in Ras-like without CAAX 1 (RIT1) and mitogenactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 53 publications
(54 reference statements)
3
149
0
Order By: Relevance
“…10 In the present study, we identified 30 additional probands and 14 relatives with NS carrying a RIT1 mutation, raising the total number of reported cases to 76. Three variants predicted to be pathogenic in silico were not reported before.…”
Section: G5mentioning
confidence: 91%
See 3 more Smart Citations
“…10 In the present study, we identified 30 additional probands and 14 relatives with NS carrying a RIT1 mutation, raising the total number of reported cases to 76. Three variants predicted to be pathogenic in silico were not reported before.…”
Section: G5mentioning
confidence: 91%
“…of 106 patients without mutations in PTPTN11, SOS1, or RAF1, whereas Chen et al 10 have identified five patients with RIT1 mutations after exome sequencing of 25 patients. 10 In the present study, we identified 30 additional probands and 14 relatives with NS carrying a RIT1 mutation, raising the total number of reported cases to 76.…”
Section: G5mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the origins of these phenotypes are still poorly understood, studies of model organisms show that many of the observed structural and functional defects can indeed be mimicked by targeted introduction of mutations found in RASopathies (5). Hundreds of such mutations have already been identified, and many more are likely to be discovered by the sequencing of affected individuals (6).…”
mentioning
confidence: 99%